2015
DOI: 10.1007/s10439-015-1501-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Mass Transport in Stented Coronary Arteries

Abstract: Oxygen deficiency, known as hypoxia, in arterial walls has been linked to increased intimal hyperplasia, which is the main adverse biological process causing in-stent restenosis. Stent implantation has significant effects on the oxygen transport into the arterial wall. Elucidating these effects is critical to optimizing future stent designs. In this study the most advanced oxygen transport model developed to date was assessed in two test cases and used to compare three coronary stent designs. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These studies have also examined the importance of non-Newtonian blood flow modelling on transport and found non-Newtonian effects to be of minor importance. For models of oxygen transport, the early paper of Crawford et al [88], followed by the study of Moore & Ethier [89] and more recently Murphy et al [90] are representative of developments in oxygen transport modelling. Tarbell [91] presented a simplified single layer model that is summarized in figure 4.…”
Section: Transport From the Lumenmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have also examined the importance of non-Newtonian blood flow modelling on transport and found non-Newtonian effects to be of minor importance. For models of oxygen transport, the early paper of Crawford et al [88], followed by the study of Moore & Ethier [89] and more recently Murphy et al [90] are representative of developments in oxygen transport modelling. Tarbell [91] presented a simplified single layer model that is summarized in figure 4.…”
Section: Transport From the Lumenmentioning
confidence: 99%
“…However, PTA with stenting is often complicated by in-stent restenosis secondary to neointimal hyperplasia, which may result in failure of the implant. Although restenosis is linked to different aspects of the procedure, recent studies have highlighted the relationship between reduced levels of oxygen tension within the stented artery wall and intimal hyperplasia [90,[104][105][106][107]. The stent itself plays a key role in determining the overall oxygen supply to the underlying tissue.…”
Section: Stent Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…In numerous previous computational studies of oxygen mass transfer in blood vessels, two approaches were utilized: (i) oxygen transport as a free species in plasma [ 7 , 23 , 26 , 29 , 30 , 33 , 34 ] and (ii) oxygen transport by haemoglobin [ 27 , 28 , 31 , 32 , 35 , 36 ]. It was suggested that the inclusion of haemoglobin-mediated oxygen transport was essential to obtain a proper representation of oxygen mass transfer in blood vessels [ 27 ].…”
Section: Introductionmentioning
confidence: 99%